Soledad, envejecimiento y viudez en el curso de la vida. Un estudio de casos en personas viudas de Argentina (2021)
This article explores ways of coping with widowhood throughout life course, analyzing differences in cohorts and gender around the subjective feeling of loneliness. It also explores the activities abandoned, changed and initiated by people post-widowhood, in addition to the types of perceived social support. Based on a qualitative methodological strategy, in-depth interviews were conducted with widowed people from Buenos Aires Metropolitan Area (Área Metropolitana de Buenos Aires), Argentina. The analysis allowed reconstructing the differences in the experience of widowhood in relation to cohort, position and gender, as well as the spatial and temporal dimensions related to the feeling of loneliness. It becomes apparent that women have a diversity of resourcesand better emotional support to cope with loneliness, when compared to widowers. Sexual division of labor is significant among widowed people born between 1930 and 1959, while the cohorts born after 1960 show more flexibility on this subject